CONSTITUTIONAL AMENDMENTS RESULTING FROM NECESSITY – A CRITICAL OVERVIEW OF THE CONSTITUTIONAL REFORMS OF THE JUDICIARY - Simovic, Darko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Following the referendum which took place on January 16, 2022, in which most citizens voted in favor of constitutional amendments; the National Assembly proclaimed the Constitutional Amendments on February 9. Although not a generally accepted view, there has been emphasis on these amendments as having improved the constitutional framework of the judiciary. Changes include the elimination of the three-year probationary mandate for judges and the election of all judges and court presidents to be under the exclusive jurisdiction of the High Judicial Council. The election process of the members of the High Judicial Council have also been depoliticized. In addition, the constitutional guarantee of the independence of judges have been improved, by securing the permanency of tenure of judicial office, constitutionalizing the basis for the removal of judges and more precise guaranteeing of their irremovability. Despite this, most scholars remain critical or at least evidently reserved with respect to the effects of the implemented constitutional changes. Aside from a deficit in democratic legitimacy in the convocation of the National Assembly who had decided upon the Constitutional Amendments, there is emphasis on the fact that the guarantees of the independence of the judiciary have only been partially improved with the creation of the new, and best described as hidden channels for political influence. Hence, a contextual analysis of the content of these constitutional amendments show that the implemented constitutional reform cannot have positive effects on the advancement of the rule of law in Serbia.